Enhancing social cognition in psychosis – the potential role of open dialogue - Maria Gariup; Tomi Bergström; Katharina Saliger; Justin M. Palanci; Robert O. Cotes; Joseph B. Stoklosa; Jaakko Seikkula (Schizophrenia)
Research in psychotic conditions increasingly focuses on improving functional outcomes. While antipsychotic treatments can alleviate positive symptoms in some patients, they have limited impact on psychosocial function. Social cognition (SC) has emerged as a promising target for intervention, with multiple new approaches designed to enhance SC in psychotic conditions. However, the generalisability of these interventions to real-world functioning remains uncertain. We propose that the Finnish Open Dialogue (OD) approach may offer unique advantages for improving SC in individuals with psychosis and their families and suggest this as an important direction for future research. This commentary aims to bridge perspectives from SC research and OD practice, proposing avenues for integration and future research.